13.9k views
4 votes
Dy/dt = y^2

y(t) = ?

1 Answer

4 votes

Answer:


y(t) = \displaystyle(-1)/(t + c)

Explanation:


(dy)/(dt) = y^2


(dy)/(y^2) = dt

If we integrate both the sides, we can get y(t)

Integrating, both sides, we get


\displaystyle\int \displaystyle(dy)/(y^2)= \int dt


\displaystyle(y^(-1))/(-1) = t + c

where, c is the integration constant.


\displaystyle(-1)/(y) = t + c


y = \displaystyle(-1)/(t + c)

Thus, the obtained y(t) is


y(t) = \displaystyle(-1)/(t + c)

User Thatdankent
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.